Overexpression of MnSOD Protects against Cold Storage-Induced Mitochondrial Injury but Not against OMA1-Dependent OPA1 Proteolytic Processing in Rat Renal Proximal Tubular Cells - Julia Tobacyk; Grishma KC; Lee Ann MacMillan-Crow (MDPI AG, 2021)
Kidneys from deceased donors undergo cold storage (CS) preservation before transplantation. Although CS is a clinical necessity for extending organ quality preservation, CS causes mitochondrial and renal injury. Specifically, many studies, including our own, have shown that the triggering event of CS-induced renal injury is mitochondrial reactive oxygen species (mROS). Here, we explored the role of OMA1-depedent OPA1 proteolytic processing in rat kidney proximal tubular epithelial (NRK) cells in an in vitro model of renal CS (18 h), followed by rewarming (6 h) (CS + RW). The involvement of mROS was evaluated by stably overexpressing manganese superoxide dismutase (MnSOD), an essential mitochondrial antioxidant enzyme, in NRK cells. Western blots detected rapid OPA1 proteolytic processing and a decrease in ATP-dependent cell viability in NRK cells subjected to CS + RW compared to control cells. Small interfering RNA (siRNA) knockdown of OMA1 reduced proteolytic processing of OPA1, suggesting that OMA1 is responsible for OPA1 proteolytic processing during CS + RW-induced renal injury. Overexpression of MnSOD during CS + RW reduced cell death, mitochondrial respiratory dysfunction, and ATP-dependent cell viability, but it did not prevent OMA1-dependent OPA1 processing. These data show for the first time that OMA1 is responsible for proteolytically cleaving OPA1 in a redox-independent manner during renal cell CS.